(untitled) (Journal of National Institute of Ophthalmology, 2026)
Background: Cataract surgery, a widespread ophthalmic procedure, addresses cloudy lenses to restore clear vision and improve the lives of millions worldwide. Sutured SFIOL, is typically used for complicated cataract cases. In contrast, sutureless SFIOL relies on innovative techniques like iris fixation or anterior chamber placement. Objectives: Aimed to assess the visual outcome after implantation of sutured and sutureless scleral fixated intra ocular lens during the management of aphakia. Methods: Prospective observational study was conducted from July 2022 to June 2023 among patients with aphakia without capsular support in the inpatient department of vitreo-retina, NIO&H, Dhaka. Randomly selected 70 patients were able to complete the follow-up during study period. Upon obtaining their informed written consent they were divided into two groups by lottery method, group I (Sutured SFIOL; n=35) and group II (Suture less; n=35). Preoperative visual acuity, slit lamp examination, fundus examination were done for both groups. Follow-up was done on 7th and 45th post-operative day. Statistical analysis was performed using SPSS software (v26.0). Statistical significance was set at p-value ≤ 0.05. Results: In group I (sutured) majority were male 19 (54.3%) and 16 (45.7%) were female and in group II (sutureless) more than half were male 20 (57.1%) and 15 (42.9%) were female. The mean (±SD) age was similar in both groups of sutured (52.06±4.3) and suture less (51.89±4.2) SFIOL procedures. Mean (±SD) post-operative intraocular pressure (IOP) at 45th day in group I was (16.2±1.4) and group II was (15.8±1.3) showed no significant difference. Aphakia was the most common lens status in both groups in group I (82.9%) and group II (71.4%). The most frequent per-operative complication was hyphema 7 (20.0%) patients in group I and 4 (11.42%) patients in group II. Common post-operative complications included Decentration 2 (5.71%) and cystoid macular oedema 2 (5.71%) patients in group I and in group II had Decentration 1 (2.85%) and Cystoid macular oedema 1 (2.85%) patient. There was a significant difference in operation time, with the group II (sutureless) having shorter surgery duration, mean (±SD) operation time was 47.1±4.7 minutes. A significant difference was noted in visual acuity at 45th postoperative day, with the group II (sutureless) exhibiting slightly better visual acuity, mean (±SD) was 0.34±o.116 in LogMAR unit than group I (sutured) mean (±SD) was 0.43±0.175 (P=0.013). Conclusion: This study showed that most of the patients experience satisfactory visual outcome following SFIOL implantation. Among the two methods used in this study visual outcome was found to be better in sutureless SFIOL group than sutured SFIOL group during the aphakic management. J.Natl.Inst.Ophthalmol.2024;7(1): 49-56